Negative electrode for lithium secondary battery and lithium secondary battery including same
By adopting a multi-layered carbon-based negative electrode active material layer in lithium secondary batteries and optimizing the stacking sequence using DD value, the problems of electrolyte impregnation and lithium ion transmission during high-rate charging and discharging of lithium secondary batteries are solved, and the problem of electrolyte impregnation and lithium ion transmission during high-rate charging and discharging of lithium secondary batteries is improved. Battery performance and lifespan.
Patent Information
- Application Number
- CN202411320666.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-24
- Filing Date
- 2020-04-17
- Publication Date
- 2024-12-27
AI Technical Summary
The negative electrode materials of existing lithium secondary batteries have problems such as electrolyte impregnation deterioration and lithium ion transmission path extension during high-rate charging and discharging, resulting in poor battery performance and cycle life characteristics.
Using a carbon-based negative electrode active material layer with a multi-layer structure, wherein at least one layer is an orientation layer with a DD value of 19 or more, the stacking sequence and structure are optimized by CuKα ray XRD measurement to ensure good impregnation of the electrolyte and efficient transmission of lithium ions.
It improves the high-rate performance and cycle life characteristics of lithium secondary batteries, reduces the ion and electronic impedance of the electrodes, and enhances the battery's high-power application capabilities.
Smart Images

Figure CN119208559A_ABST
Abstract
Description
[0001] This application is a divisional application of the patent application with the application date of April 17, 2020, application number 202080030569.6 (international application number PCT / KR2020 / 005152), and title "Negative electrode for lithium secondary battery and lithium secondary battery including the same". Technical Field
[0002] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same. Background Art
[0003] Lithium secondary batteries have recently received attention as power sources for small portable electronic devices, and since lithium secondary batteries use an organic electrolyte solution, the discharge voltage of lithium secondary batteries is twice or more that of conventional batteries using an alkaline aqueous solution, and thus lithium secondary batteries have a high energy density.
[0004] For the positive electrode active material of rechargeable lithium batteries, oxides including lithium and transition metals and having a structure capable of inserting / extracting lithium ions, such as LiCoO2, LiMn2O4, LiNi 1-x Co x O2 (0 < x < 1), etc., have been mainly used.
[0005] For the negative electrode active material, various carbon-based materials (such as artificial graphite, natural graphite, hard carbon, etc.) capable of inserting / extracting lithium ions have been used, and in order to obtain a high capacity, non-carbon-based negative electrode active materials (such as silicon or tin) have recently been studied. Summary of the Invention
[0006] Technical Problem
[0007] One embodiment provides a negative electrode for a lithium secondary battery, which exhibits excellent physical properties such as good adhesion and good electrolyte impregnation.
[0008] Another embodiment provides a lithium secondary battery including the negative electrode.
[0009] Technical Solution
[0010] One embodiment provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery including: a current collector; and a negative electrode active material layer including a carbon-based negative electrode active material, wherein the negative electrode active material layer has a multilayer structure of three or more layers, and at least one layer in the negative electrode active material layer is an oriented layer having a DD (divergence degree) value of 19 or more defined by Equation 1.
[0011] [Equation 1]
[0012] DD (divergence degree) = (Ia / I 总 )×100
[0013] (In Equation 1,
[0014] I a is the sum of the peak intensities at non-planar angles measured by XRD using CuKα radiation, and
[0015] I 总 It is the sum of the peak intensities at all angles measured by XRD using CuKα radiation. )
[0016] The negative electrode active material layer may have a multilayer structure of three layers or five layers.
[0017] The negative active material layer having a multilayer structure of three or more layers may have an inner layer in contact with a current collector, a surface layer, and at least one intermediate layer between the inner layer and the surface layer, and the surface layer may be an alignment layer having a DD value of 19 or more.
[0018] The alignment layer may have a DD value of 19 to 60.
[0019] I a may be the sum of the peak intensities at 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2° measured by XRD using CuKα rays, and I 总 It may be the sum of peak intensities at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° measured by XRD using CuKα rays.
[0020] The peak intensity can be a peak integrated area value.
[0021] At least one layer of the negative active material layers may be an oriented layer having a DD value of 19 or more, and at least one layer may be a non-oriented layer having a DD value of less than 19.
[0022] When measured by XRD using CuKα radiation, the peak intensity ratio of the negative electrode at the (002) plane relative to the (110) plane (i.e., I (002) / I (110) ) can be from 50 to 300.
[0023] When measured by XRD using CuKα radiation, the peak intensity ratio of the oriented layer at the (002) plane relative to the (110) plane (i.e., I (002) / I (110)) may be 10 to 200. When measured by XRD using CuKα rays, the peak intensity ratio of the non-oriented layer at the (002) plane relative to the (110) plane (i.e., I (002) / I (110) ) can be from 200 to 500.
[0024] The negative active material layer may have a total thickness of 100 μm to 1000 μm.
[0025] The carbon-based negative electrode active material may be artificial graphite or a mixture of artificial graphite and natural graphite.
[0026] In addition, the negative electrode active material layer may further include Si-based negative electrode active materials, Sn-based negative electrode active materials, lithium vanadium oxide, or a combination thereof.
[0027] Another embodiment provides a lithium secondary battery including a negative electrode, a positive electrode including a positive electrode active material, and an electrolyte.
[0028] Lithium secondary batteries can be used for high power.
[0029] Other embodiments are included in the detailed description below.
[0030] Beneficial Effects
[0031] The negative electrode for a lithium secondary battery according to one embodiment may provide a lithium secondary battery exhibiting excellent battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a schematic diagram showing the orientation according to an embodiment of the present invention.
[0033] Figure 2 is a schematic diagram showing the structure of a negative electrode according to one embodiment of the present invention.
[0034] Figure 3 is a schematic diagram of the orientation of the negative electrode according to one embodiment of the present invention.
[0035] Figure 4 is a schematic diagram showing the structure of a lithium secondary battery according to one embodiment. DETAILED DESCRIPTION
[0036] Hereinafter, embodiments of the present invention are described in detail. However, these embodiments are exemplary, the present invention is not limited thereto, and the present invention is defined by the scope of the claims.
[0037] According to one embodiment of the present invention, the negative electrode includes a current collector and a negative electrode active material layer formed on the current collector and including a carbon-based negative electrode active material, the negative electrode active material layer has a multilayer structure of three or more layers, and at least one layer of the negative electrode active material layer is an oriented layer with a DD (Degree of Divergence) value of 19 or more.
[0038] The DD value can be defined by Equation 1.
[0039] [Equation 1]
[0040] DD(divergence)=(I a / I 总 )×100
[0041] In equation 1,
[0042] I a is the sum of the peak intensities at non-planar angles measured by XRD using CuKα radiation,
[0043] I 总 is the sum of the peak intensities at all angles measured by XRD using CuKα radiation.
[0044] Here, when measured by XRD using CuKα rays, the non-plane angles represent 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2°, that is, (100) plane, (101)R plane, (101)H plane, and (110) plane. Generally, graphite has a structure classified into a rhombus structure and a hexagonal structure having an ABAB type stacking order according to the stacking order of graphene layers, the R plane represents the rhombus structure, and the H plane represents the hexagonal structure.
[0045] In addition, when measured by XRD using CuKα rays, all angles (representing 2θ = 26.5 ± 0.2°, 42.4 ± 0.2°, 43.4 ± 0.2°, 44.6 ± 0.2°, 54.7 ± 0.2° and 77.5 ± 0.2°, i.e., (002) plane, (100) plane, (101) R plane, (101) H plane, (004) plane and (110) plane. The peak at 2θ = 43.4 ± 0.2° can also be considered to appear because the peak of the (101) R plane of the carbon-based material overlaps with another peak of the (111) plane of the current collector (e.g., Cu).
[0046] Generally, the peak intensity indicates the height of the peak or the integrated area of the peak. According to an embodiment, the peak intensity indicates the integrated area of the peak.
[0047] In the embodiment, XRD is measured by using CuKα rays as target rays under the measurement conditions of 2θ=10° to 80°, a scanning speed (° / S) of 0.044 to 0.089 and a step size (° / step) of 0.013 to 0.039, but the monochromator is removed to improve the peak intensity resolution.
[0048] The DD value indicates that the negative electrode active material included in the negative electrode active material layer is oriented at a predetermined angle, and a larger value indicates that the negative electrode active material is well oriented. Figure 1 As schematically shown in FIG. 1 , when the negative electrode active material 3 is oriented toward one side of the substrate 1 at an angle (α), the angle (α) increases as the DD value increases. In addition, the DD value is maintained after charge and discharge.
[0049] In one embodiment, the DD value may be 19 to 60, or may be 19 to 40. The DD value of the alignment layer satisfying the above range indicates that the negative active material is aligned at a predetermined angle, which is maintained after charge and discharge.
[0050] When the DD value of the orientation layer is greater than 19, the negative electrode active material is not horizontally oriented relative to the current collector, but is sufficiently oriented to easily transfer lithium ions, that is, the negative electrode active material is arranged at a predetermined angle relative to the current collector, for example, it indicates that the (002) plane of graphite is arranged at an angle greater than 0 degrees (°) and less than 90 degrees (°), which indicates that the non-orientation is controlled, and a DD value less than 19 increases the DC internal resistance, sharply deteriorates the rate performance (especially high rate performance), and deteriorates the cycle life characteristics. In addition, a DD value of 19 or more and 60 or less does not indicate that the negative electrode active material is substantially vertically oriented relative to the current collector, and if it is vertically oriented, disadvantages such as battery deformation may occur with repeated charging and discharging processes.
[0051] The negative electrode active material layer may have a multilayer structure of three or more layers. In one embodiment, the negative electrode active material layer may have a multilayer structure of three to five layers. In the multilayer structure, at least one layer may be an oriented layer having a DD value of 19 or more.
[0052] Here, the negative electrode active material layer having a multilayer structure of three or more layers may include an inner layer contacting a current collector, a surface layer, and at least one intermediate layer between the inner layer and the surface layer, and it is desirable that the surface layer is an alignment layer having a DD value of 19 or more. Figure 2 As shown, the negative electrode 30 has a structure in which a current collector 32 , an inner layer 34 , an intermediate layer 36 , and a surface layer 38 are sequentially stacked, and here, the surface layer 38 is an oriented layer having a DD value of 19 or more.
[0053] When the surface layer is an oriented layer, that is, having a high degree of orientation of the negative electrode active material, the negative electrode active material is not oriented horizontally and parallel to the current collector, but is positioned in an upright state at a predetermined angle to the current collector, which allows easy infiltration of the electrolyte into the negative electrode active material layer, thereby easily transporting lithium ions and shortening the transmission path. Therefore, the resulting negative electrode can be appropriately used as a high-power battery and can exhibit excellent high-rate performance characteristics.
[0054] If the surface layer is not an oriented layer, that is, a non-dispersed non-oriented layer indicating various modes in which the negative electrode active material is oriented horizontally and parallel to the current collector or positioned vertically relative to the current collector, the impregnation of the electrolyte will deteriorate and the transmission path of lithium ions will increase, and therefore, it may not be suitable for use as a high-power battery.
[0055] In the negative electrode active material layer, at least one layer may be an oriented layer having a DD value of 19 or more, and at least one layer may be a non-oriented layer having a DD value of less than 19. In this way, when the negative electrode active material layer has a multilayer structure of three or more layers and has both an oriented layer and a non-oriented layer, the uniformity of the reaction in the same layer can be ensured, and the migration of the binder can be suppressed during drying, so that the cohesive force at the boundary portion between the oriented layer and the non-oriented layer can be increased to improve adhesion, and the electronic impedance of the active material layer (including the active material, the binder and the optional conductive material, and refers to the active material layer on the current collector) can be reduced, and the ionic impedance of the negative electrode can be reduced. Even if the negative electrode active material layer has a multilayer structure, if the oriented portion and the non-oriented portion exist together in the same layer instead of in separate layers, during drying, migration of the binder occurs in the oriented portion / non-oriented portion, resulting in reduced adhesion, increased ionic impedance of the negative electrode, and different impregnation of the electrolyte in the oriented portion from that in the non-oriented portion, thereby increasing the non-uniformity of the reaction and causing local non-uniformity of thickness when fully charged and precipitation of lithium during charging at a high rate.
[0056] In addition, even if the negative electrode active material layer has a multilayer structure and has an oriented layer and a non-oriented layer, if the structure is a two-layer structure (i.e., an oriented layer and a non-oriented layer), it is difficult to suppress the migration of the binder during drying, so that the ionic impedance and electronic impedance of the active material layer in the electrode will increase.
[0057] According to one embodiment, the negative electrode active material layer may include three layers or more, or three to five layers, and if the number of layers is an odd number, when the surface is referred to as the first layer, the oriented layer may correspond to the first layer, the third layer and the fifth layer, and the non-oriented layer may correspond to the second layer and the fourth layer.
[0058] Furthermore, when the negative electrode active material layer includes four layers, the first layer and the fourth layer may be alignment layers, and the second layer and the third layer may be non-alignment layers.
[0059] When measured by XRD using CuKα radiation, the peak intensity ratio of the negative electrode at the (002) plane relative to the (110) plane (i.e., I (002) / I (110) ) can be 50 to 300. When the negative electrode I (002) / I (110) When the above range is satisfied, a reduction in internal resistance, improvements in high rate performance and cycle life characteristics, and a reduction in the active material layer in the electrode can be achieved.
[0060] In addition, when measured by XRD using CuKα radiation, the peak intensity ratio of the oriented layer at the (002) plane relative to the (110) plane (i.e., I (002) / I (110) ) can be 10 to 200. When the orientation layer I (002) / I (110) When the above range is satisfied, a reduction in internal resistance, improvements in high rate performance and cycle life characteristics, and a reduction in the active material layer in the electrode can be achieved.
[0061] When measured by XRD using CuKα radiation, the peak intensity ratio of the non-oriented layer at the (002) plane relative to the (110) plane (i.e., I (002) / I (110) ) can be 200 to 500. When the non-oriented layer has (002) / I (110) When the content is within this range, contact between active material particles may be increased to reduce impedance of the active material in the electrode.
[0062] In the embodiment, since the DD value is the peak value at the non-plane relative to the peak value at all angles, it is not related to I (002) / I (110) Therefore, the I between 50 and 300 (002) / I (110) It does not mean that the DD values of the first layer and the second layer are within the above range.
[0063] In addition, the total thickness of the negative electrode active material layer may be 100 μm to 1000 μm. In this way, the negative electrode active material layer may be formed with a maximum thickness of 1000 μm, which is much greater than the general maximum thickness of 70 μm of the negative electrode active material layer. The negative electrode active material layer is a multilayer structure of three or more layers, which is desirable if the total thickness of all active material layers falls within this range, but the thickness of each layer is not limited. In one embodiment, the negative electrode active material layer is formed as a multilayer structure of three or more layers, where the DD value of the surface layer is controlled to be 19 or more to improve the impregnation of the electrolyte, so that even if a thick layer is formed, high rate charge and discharge can be effectively performed, and therefore, it can be appropriately applied to high power batteries.
[0064] In one embodiment, the DD value is obtained by the following steps: charging and discharging a rechargeable lithium battery including a negative electrode; disassembling the battery to obtain the negative electrode when fully discharged; and measuring the negative electrode by XRD. Here, charging and discharging are performed once or twice at about 0.1C to about 0.2C.
[0065] The BET specific surface area of the negative electrode can be less than about 5.0 m 2 / g, or about 0.6m 2 / g to about 2.0m 2 / g. When the BET specific surface area of the negative electrode is less than about 5.0 m 2 / g, the electrochemical cycle life characteristics of the battery can be improved. In an embodiment, BET can be measured by a nitrogen adsorption method by the following steps: charging and discharging a lithium secondary battery including a negative electrode; fully discharging the battery to less than or equal to about 3V; disassembling the battery to obtain the negative electrode; cutting the negative electrode into a predetermined size; and placing the cut negative electrode in a BET sample holder.
[0066] The negative electrode may have a 2 To about 65mg / cm 2 The cross-sectional load level (L / L).
[0067] In the negative electrode active material, the carbon-based negative electrode active material can be artificial graphite or a mixture of artificial graphite and natural graphite. When the negative electrode active material is a crystalline carbon-based material (such as artificial graphite or a mixture of natural graphite and artificial graphite), the crystalline carbon-based material has a more developed crystallization property than the amorphous carbon-based active material, and thus the orientation property of the carbon material in the electrode relative to the external magnetic field can be further improved. Artificial graphite or natural graphite can be amorphous, plate-shaped, sheet-shaped, spherical, fibrous or a combination thereof, without particular limitation. In addition, artificial graphite is mixed with natural graphite in a ratio of about 70wt%:30wt% to about 95wt%:5wt%.
[0068] In addition, the negative electrode active material layer may include at least one non-carbon-based material selected from Si-based negative electrode active materials, Sn-based negative electrode active materials, or lithium vanadium oxide negative electrode active materials. When the negative electrode active material layer further includes these materials (i.e., a carbon-based negative electrode active material as the first negative electrode active material and a non-carbon-based material as the second negative electrode active material), the first negative electrode active material and the second negative electrode active material may be mixed in a weight ratio of about 50:50 to about 99:1.
[0069] The Si-based negative electrode active material may be Si, Si-C composite, SiO x (0 < x < 2) and Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, but not Si), the Sn-based negative electrode active material is selected from Sn, SnO2, Sn-R alloy (where R is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, but not Si), etc., and the Sn-based negative electrode active material is also selected from mixtures of at least one of them with SiO2. The elements Q and R may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0070] In the negative electrode active material layer, based on the total weight of each layer, the amount of the negative electrode active material may be about 95 wt% to about 99 wt%, such that it may be about 95 wt% to about 99 wt% based on the total weight of the negative electrode active material layer.
[0071] The negative electrode active material layer includes a binder and may also include a conductive material. In the negative electrode active material layer, based on the total weight of the negative electrode active material layer, the amount of the binder may be about 1 wt% to about 5 wt%. Additionally, when further including a conductive material, it may include about 90 wt% to about 98 wt% of the negative electrode active material, about 1 wt% to about 5 wt% of the binder, and about 1 wt% to about 5 wt% of the conductive material.
[0072] The binder improves the binding properties between the negative electrode active material particles and the binding properties between the negative electrode active material particles and the current collector. The binder may be a non-aqueous binder, an aqueous binder, or a combination thereof.
[0073] The non-aqueous binder may be ethylene propylene copolymer, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0074] The aqueous binder can be styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber (ABR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol or a combination thereof.
[0075] When an aqueous binder is used as a negative electrode binder, a cellulose compound may also be used to provide viscosity as a thickener. The cellulose compound includes one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts. The alkali metal may be Na, K, or Li. The thickener may be included in an amount of about 0.1 to about 3 parts by weight based on 100 parts by weight of the negative electrode active material.
[0076] The conductive material is included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may be: a carbon-based material such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; a metal-based material including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; a conductive polymer such as a polyphenylene derivative; or a mixture thereof.
[0077] The current collector may include one selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof, but is not limited thereto.
[0078] The negative electrode according to one embodiment may be prepared by applying a magnetic field when coating the negative electrode active material composition on a current collector. Figure 3 The preparation of a negative electrode active material layer (for example, a negative electrode active material layer having three layers) is described.
[0079] like Figure 3 As shown in , the current collector 1 is disposed on the magnet 7, and a first layer composition including a negative electrode active material 3 is coated on the current collector 1. After coating the first layer composition, drying is performed to prepare a first layer U1. Thereafter, a second layer composition including a negative electrode active material is coated on the first layer and dried to prepare a second layer U2, and a third layer composition including a negative electrode active material is coated on the second layer and dried to prepare a third layer U3.
[0080] The negative electrode active material 3 included in the third layer U3 is an orientation layer in which the negative electrode active material is oriented at a predetermined angle with respect to the current collector, and since the surface layer as the orientation layer is an important factor, Figure 3 Only the negative electrode active material 3 oriented in the third layer U3 is shown, and the orientation state of the negative electrode active materials included in the first layer and the second layer is not shown.
[0081] The magnet may have a magnetic field strength of about 1000 gauss to about 10000 gauss. In addition, the negative active material composition may be coated on the current collector, and the negative active material composition may be maintained for about 3 seconds to about 9 seconds, that is, the negative active material composition may be exposed to the magnetic field for about 3 seconds to about 9 seconds.
[0082] When such magnetic field application is performed, especially when the coating process is performed while the current collector is moved, a magnetic field (magnetic flux) formed by the magnet can be formed vertically with respect to the current collector, but since the magnetic field is formed at a predetermined angle as a vector function according to the coating speed (the speed of moving the current collector), the negative active material included in the first layer composition and the second layer composition can stand up on the surface of the current collector, that is, be oriented at a predetermined angle on the surface of the current collector.
[0083] In particular, when the coating process is performed while the current collector is moved, a magnetic field (magnetic flux) formed by the magnet can be formed vertically with respect to the current collector, but since the magnetic field is formed at a predetermined angle as a vector function according to the coating speed (speed of moving the current collector), the negative active material included in the negative active material composition can stand up on the surface of the current collector, that is, be oriented at a predetermined angle on the surface of the current collector.
[0084] Here, even if the same magnetic field is applied to the preparation of the first layer, the preparation of the second layer, and the preparation of the third layer, the viscosity of the first layer composition, the second layer composition, and the third layer composition is adjusted to form the first layer, the second layer, and the third layer having different DD values from each other. That is, in the preparation of a multilayer structure of three or more layers, it is desirable to adjust the viscosity of the composition for preparing the layer to be an oriented layer or a non-oriented layer to prepare each layer.
[0085] In order to prepare a layer to be formed as an alignment layer, the viscosity of the composition should be 2000cps or more and less than 4000cps at room temperature (about 20°C to about 25°C), and in order to prepare a layer to be formed as a non-aligned layer, the viscosity of the composition should be 4000cps to 5000cps at room temperature (about 20°C to about 25°C). In particular, when the viscosity of the composition falls within the range of 2000cps or more and less than 4000cps at room temperature (about 20°C to about 25°C), the prepared layer may be an alignment layer having a DD value of 19 or more, and more specifically, when the viscosity of the composition falls within the range of 2000cps to 3500cps at room temperature (about 20°C to about 25°C), the prepared layer may be an alignment layer having a DD value of 19 to 60.
[0086] In addition, when the viscosity of the composition is 4000 cps to 5000 cps at room temperature (about 20° C. to about 25° C.), the prepared layer may be a non-oriented layer having a DD value of less than 19.
[0087] Thus, if they are outside the range, a desired degree of orientation will not be obtained.
[0088] The composition may be prepared by mixing a negative electrode active material, a binder, and a conductive material in a solvent.
[0089] The negative electrode active material, the binder and the conductive material are the same as described above. The solvent may be an organic solvent such as N-methylpyrrolidone or water, and when an aqueous binder is used as the binder, the solvent may be water.
[0090] A lithium secondary battery according to another embodiment includes a negative electrode, a positive electrode, and an electrolyte.
[0091] A lithium secondary battery can be a battery for high power. In other words, a lithium secondary battery can be effectively applied to electronic devices that require high power, such as power tools, electric vehicles, vacuum cleaners, and the like. The reason is that the lithium secondary battery including a negative electrode according to the embodiment can easily release the heat generated during charging and discharging, and in particular, when it is applied to a high-capacity battery and an electronic device for high power, the degradation due to heat can be suppressed, and it can be effectively used as a high-power battery. In addition, the lithium secondary battery can easily release the heat according to charging and discharging, and the battery temperature rise can be suppressed, thereby effectively improving the cycle life characteristics, especially the cycle life characteristics at high rates.
[0092] The high-power battery can be a cylindrical pouch battery or a stacked battery. In addition, the cylindrical battery can be a 18650 battery (18 mm in diameter and 65 mm in height) and a 21700 battery (21 mm in diameter and 70 mm in height), but is not limited thereto.
[0093] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. Specifically, one or more composite oxides of a metal selected from cobalt, manganese, nickel, and a combination thereof and lithium may be used. More specifically, a compound represented by one of the following chemical formulas may be used. Li a A 1-b X b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a E 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a E 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α≤2); Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b X c D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn bX c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05\0<α<2);Li a Nor 1-b-c Mn b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Nor b E c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Nor b Co c Mn d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0.001≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-b G b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G b O4(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-g G g PO4(0.90≤a≤1.8,0≤g≤0.5);QO2;QS2;LiQS2;V2O5;LiV2O5;LiZO2;LiVO4;Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4(0.90≤a≤1.8)。
[0094] In the above chemical formula, A is selected from Ni, Co, Mn and combinations thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and combinations thereof; D is selected from O, F, S, P and combinations thereof; E is selected from Co, Mn and combinations thereof; T is selected from F, S, P and combinations thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and combinations thereof; Q is selected from Ti, Mo, Mn and combinations thereof; Z is selected from Cr, V, Fe, Sc, Y and combinations thereof; and J is selected from V, Cr, Mn, Co, Ni, Cu and combinations thereof.
[0095] In addition, the compound may have a coating layer located on the surface, or may be mixed with another compound having a coating layer. The coating layer may include at least one coating element compound selected from the group consisting of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound for the coating layer may be amorphous or crystalline. The coating element included in the coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating layer may be provided by using these elements in the compound in a method that has no adverse effect on the properties of the positive active material, for example, the method may include any coating method (such as spraying, dipping, etc.), but since it is well known in the relevant art, it is not described in more detail.
[0096] In the positive electrode, the content of the positive electrode active material may be 90 wt % to 98 wt % based on the total weight of the positive electrode active material layer.
[0097] In an embodiment, the positive active material layer may further include a binder and a conductive material. Here, the binder and the conductive material may be included in an amount of about 1 wt % to about 5 wt % based on the total amount of the positive active material layer.
[0098] The binder improves the bonding properties of the positive electrode active material particles to each other and to the current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0099] The conductive material is included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0100] The current collector may use Al, but is not limited thereto.
[0101] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0102] The nonaqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.
[0103] The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, or an aprotic solvent.
[0104] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. In addition, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and examples of aprotic solvents include nitriles such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, cyclopentane, etc.
[0105] The organic solvent may be used alone or in a mixture. When the organic solvent is used in a mixture, the mixing ratio may be controlled according to the desired battery performance, and the mixing ratio may be well known to those skilled in the relevant art.
[0106] In addition, the carbonate-based solvent may include a mixture of cyclic carbonate and chain carbonate. The cyclic carbonate and chain carbonate are mixed together in a volume ratio of about 1:1 to about 1:9, and when the mixture is used as an electrolyte, it may have enhanced performance.
[0107] In addition to the carbonate-based solvent, the organic solvent may further include an aromatic hydrocarbon-based solvent. Here, the carbonate-based solvent and the aromatic hydrocarbon-based solvent may be mixed together in a volume ratio of about 1:1 to about 30:1.
[0108] The aromatic hydrocarbon solvent may be an aromatic hydrocarbon compound represented by Chemical Formula 1.
[0109] [Chemical formula 1]
[0110]
[0111] (In Chemical Formula 1, R1 to R6 are the same or different and are selected from hydrogen, halogen, C1 to C10 alkyl, halogenated alkyl, and combinations thereof.)
[0112] Specific examples of aromatic hydrocarbon solvents can be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, , 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.
[0113] The electrolyte may further include an additive of vinylene carbonate, an ethylene carbonate-based compound represented by Chemical Formula 2, or propane sultone to improve cycle life.
[0114] [Chemical formula 2]
[0115]
[0116] (In Chemical Formula 2, R7 and R8 are the same or different and may be independently hydrogen, halogen, cyano (CN), nitro (NO2) and fluorinated C1 to C5 alkyl, provided that at least one of R7 and R8 is halogen, cyano (CN), nitro (NO2) or fluorinated C1 to C5 alkyl, and R7 and R8 are not hydrogen at the same time.)
[0117] Examples of ethylene carbonate compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. The amount of the additive for improving the cycle life can be flexibly used within a suitable range.
[0118] The lithium salt dissolved in the organic solvent supplies lithium ions to the battery, enables the basic operation of the lithium secondary battery, and improves the transmission of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein, x and y are natural numbers, for example, integers of 1 to 20), at least one supporting salt of LiCl, LiI, and LiB(C2O4)2 (lithium bis(oxalato)borate: LiBOB). The concentration of the lithium salt may range from about 0.1 M to about 2.0 M. When the lithium salt is included in the above concentration range, the electrolyte may have excellent performance and lithium ion mobility due to optimal electrolyte conductivity and viscosity.
[0119] Depending on the type of battery, the lithium secondary battery may also include a separator between the negative electrode and the positive electrode. Examples of suitable separator materials include polyethylene, polypropylene, polyvinylidene fluoride, and multilayers thereof (such as polyethylene / polypropylene double-layer separator, polyethylene / polypropylene / polyethylene three-layer separator, and polypropylene / polyethylene / polypropylene three-layer separator).
[0120] Figure 4 is an exploded perspective view of a lithium secondary battery according to an embodiment. The lithium secondary battery according to an embodiment may be a cylindrical battery.
[0121] Reference Figure 4 The lithium secondary battery 100 is a cylindrical battery and includes a negative electrode 112 , a positive electrode 114 and a separator 113 , an electrolyte (not shown) impregnated in the negative electrode 112 , the positive electrode 114 and the separator 113 , a battery case 120 , and a sealing member 140 accommodating the battery case 120 .
[0122] Such a lithium secondary battery 100 is manufactured by sequentially stacking a negative electrode 112 , a separator 113 , and a positive electrode, winding them in a spiral form, and housing them in a battery case 120 .
[0123] Example
[0124] Hereinafter, examples and comparative examples of the present invention are described. However, these examples should not be interpreted as limiting the scope of the invention in any sense.
[0125] (Example 1: Three-layer structure having a first layer as an alignment layer and a surface layer (third layer))
[0126] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a first layer having a viscosity (at 25° C.) of 3000 cps.
[0127] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a second layer having a viscosity (at 25° C.) of 4000 cps.
[0128] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a third layer having a viscosity (at 25° C.) of 2000 cps.
[0129] The Cu foil was set on a magnet with a magnetic field strength of 4000 Gauss, and the negative active material slurry for the first layer was coated on the Cu foil while being moved to be exposed to the magnetic field for 9 seconds and dried to form a first layer with a thickness of 40 μm on one side.
[0130] Thereafter, the negative electrode active material slurry for the second layer was coated on the first layer, exposed to a magnetic field for 9 seconds, and dried to prepare a second layer with a thickness of 40 μm, and the negative electrode active material slurry for the third layer was coated on the second layer, exposed to a magnetic field for 9 seconds, and dried to prepare a third layer with a thickness of 50 μm.
[0131] After forming the first, second and third layers, the surface loading level (L / L) was 15 mg / cm 2 The negative electrode performs pressing.
[0132] 96 wt% of LiCoO2, 2 wt% of Ketjen black and 2 wt% of polyvinylidene fluoride were mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated on an Al current collector, dried and pressed to prepare a positive electrode.
[0133] The negative electrode, the positive electrode and the electrolyte were used to manufacture a 18650-type cylindrical lithium secondary battery cell having a capacity of 550 mAh and a current density of 4.70 mAh / cm2 Here, the electrolyte was prepared by using a mixed solvent of ethylene carbonate and diethyl carbonate (volume ratio of 50:50) and dissolving 1M LiPF6 therein.
[0134] (Example 2: Four-layer structure having the first layer as an alignment layer and a surface layer (fourth layer))
[0135] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a first layer having a viscosity (at 25° C.) of 3000 cps.
[0136] 97.8 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 0.7 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a second layer having a viscosity (at 25° C.) of 4000 cps.
[0137] 98.2 wt % of artificial graphite, 0.3 wt % of styrene butadiene rubber, and 1.5 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a third layer having a viscosity (at 25° C.) of 4000 cps.
[0138] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a fourth layer having a viscosity (at 25° C.) of 2000 cps.
[0139] The Cu foil was set on a magnet with a magnetic field strength of 4000 Gauss, and the negative active material slurry for the first layer was coated on the Cu foil while being moved to be exposed to the magnetic field for 9 seconds and dried to form a first layer with a thickness of 30 μm on one side.
[0140] Thereafter, the negative electrode active material slurry for the second layer was coated on the first layer, exposed to the magnetic field for 9 seconds, and dried to prepare a second layer with a thickness of 30 μm, the negative electrode active material slurry for the third layer was coated on the second layer, exposed to the magnetic field for 9 seconds, and dried to prepare a third layer with a thickness of 30 μm, and the negative electrode active material slurry for the fourth layer was coated on the third layer, exposed to the magnetic field for 9 seconds, and dried to prepare a fourth layer with a thickness of 40 μm.
[0141] After forming the first, second, third and fourth layers, a surface loading level (L / L) of 15 mg / cm 2 The negative electrode performs pressing.
[0142] A lithium secondary battery was manufactured through the same steps as in Example 1 using this negative electrode.
[0143] (Example 3: Five-layer structure having a first layer as an alignment layer, a third layer, and a surface layer (fifth layer))
[0144] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a first layer having a viscosity (at 25° C.) of 3000 cps.
[0145] 97.5 wt % of artificial graphite, 1.2 wt % of styrene butadiene rubber, and 1.3 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a second layer having a viscosity (at 25° C.) of 4000 cps.
[0146] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a third layer having a viscosity (at 25° C.) of 3000 cps.
[0147] 98.2 wt % of artificial graphite, 0.3 wt % of styrene butadiene rubber, and 1.5 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a fourth layer having a viscosity (at 25° C.) of 4000 cps.
[0148] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a fifth layer having a viscosity (at 25° C.) of 2000 cps.
[0149] The Cu foil was set on a magnet with a magnetic field strength of 4000 Gauss, and the negative active material slurry for the first layer was coated on the Cu foil while being moved to be exposed to the magnetic field for 9 seconds and dried to form a first layer with a thickness of 30 μm on one side.
[0150] Thereafter, the negative electrode active material slurry for the second layer was coated on the first layer, exposed to the magnetic field for 9 seconds, and dried to prepare a second layer with a thickness of 30 μm, the negative electrode active material slurry for the third layer was coated on the second layer, exposed to the magnetic field for 9 seconds, and dried to prepare a third layer with a thickness of 30 μm, the negative electrode active material slurry for the fourth layer was coated on the third layer, exposed to the magnetic field for 9 seconds, and dried to prepare a fourth layer with a thickness of 30 μm, and the negative electrode active material slurry for the fifth layer was coated on the fourth layer, exposed to the magnetic field for 9 seconds, and dried to prepare a fifth layer with a thickness of 30 μm.
[0151] After forming the first, second, third, fourth and fifth layers, a surface loading level (L / L) of 15 mg / cm 2 The negative electrode performs pressing.
[0152] A lithium secondary battery was manufactured through the same steps as in Example 1 using this negative electrode.
[0153] (Comparative Example 1: Double-layer structure with alignment layer and non-alignment layer)
[0154] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a first layer having a viscosity (at 25° C.) of 4500 cps.
[0155] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1.0 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry for a second layer having a viscosity (at 25° C.) of 2500 cps.
[0156] The Cu foil was set on a magnet with a magnetic field strength of 4000 Gauss, and the negative active material slurry for the first layer was coated on the Cu foil while being moved to be exposed to the magnetic field for 3 seconds and dried to form a first layer with a thickness of 60 μm on one side.
[0157] Thereafter, the negative electrode active material slurry for the second layer was coated on the first layer, exposed to a magnetic field for 9 seconds, and dried to prepare a second layer having a thickness of 70 μm.
[0158] After forming the first and second layers, the surface loading level (L / L) was 15 mg / cm 2 The negative electrode performs pressing.
[0159] A lithium secondary battery was manufactured through the same steps as in Example 1 using this negative electrode.
[0160] (Comparative Example 2: Oriented and non-oriented parts are present in the same layer)
[0161] 97.5 wt % of artificial graphite, 1.5 wt % of styrene butadiene rubber, and 1 wt % of carboxymethyl cellulose were mixed with a water solvent to prepare a negative active material slurry having a viscosity (at 25° C.) of 3000 cps.
[0162] Two magnets with a magnetic field of 4000 Gauss were fixed at a predetermined interval in the width direction of the electrode, and Cu foil was set on the magnets, and the negative electrode active material slurry for the first layer was coated on the Cu foil, while the Cu foil was moved so that it was exposed to the magnetic field for 9 seconds, and dried to form a first layer with a thickness of 130 μm on one side. In the prepared coating, any part directly located on the magnet and affected by the magnetic field was prepared as an oriented part, and any part located between the two magnets (i.e., between one magnet and the other magnet) and not affected by the magnetic field was prepared as a non-oriented part.
[0163] After coating, the surface loading level (L / L) was 15 mg / cm 2 The negative electrode performs pressing.
[0164] A lithium secondary battery was manufactured through the same steps as in Example 1 using this negative electrode.
[0165] *Measurement of X-ray diffraction characteristics
[0166] The lithium secondary batteries according to Examples 1 to 3 and Comparative Examples 1 and 2 were charged and discharged twice at 0.1C and fully discharged to 2.75V at 0.1C. The fully discharged battery cells were disassembled to obtain the negative electrodes. For these negative electrodes, an X'Pert (PANalytical BV) XRD device using CuKα rays as target rays was used, but the monochromator device was removed to improve the peak intensity resolution. Here, the measurement was performed under the conditions of 2θ = 10° to 80°, scanning speed (° / S) = 0.06436 and a step size of 0.026° / step.
[0167] From the measured XRD results, the DD values of the entire negative electrode active material layer and the first layer were calculated, and the results are shown in Table 1.
[0168] The areas of the peaks shown at 2θ=26.5±0.2° ((002) plane), 42.4±0.2° ((100) plane), 43.4±0.2° ((101) R plane), 44.6±0.2° ((101) H plane), 54.7±0.2° ((004) plane) and 77.5±0.2° ((110) plane) were measured, and the sum of the peak areas shown at 2θ=42.4±0.2° ((100) plane), 43.4±0.2° ((101) R plane), 44.6±0.2° ((101) H plane) and 77.5±0.2° ((110) plane) was taken as I aThe sum of the peak areas at 2θ = 26.5 ± 0.2° ((002) plane), 42.4 ± 0.2° ((100) plane), 43.4 ± 0.2° ((101) R plane), 44.6 ± 0.2° ((101) H plane), 54.7 ± 0.2° ((004) plane) and 77.5 ± 0.2° ((110) plane) was taken as I 总 , and DD(I 总 / I a The results are shown in Table 2.
[0169] In addition, calculate I (004) / I (002) and I (110) / I (004) , and the results are shown in Table 2. In particular, the peak at 43.4±0.2° appears because the peak of the (101) R plane of graphite overlaps with another peak of the (111) plane of the Cu current collector.
[0170] *Rate-performance characteristic evaluation
[0171] The lithium secondary batteries according to Examples 1 to 3 and Comparative Examples 1 to 2 were charged once at each of C rates of 0.2C, 0.5C, 1C, 1.5C, and 2.0C, and the capacity ratios of the respective C rates to 0.2C were measured. The results are shown in Table 3.
[0172] Table 1
[0173]
[0174] As shown in Table 1, the DD values of the negative electrodes according to Examples 1 to 3 are 28.9 to 31.1, and the DD values of the first and third layers of Example 1, the first and fourth layers of Example 2, and the first, third, and fifth layers of Example 3 fall within the range of 19 to 60, indicating an alignment layer.
[0175] Table 2
[0176]
[0177] As shown in Table 2, the peak intensity of the negative electrode is (002) / I (110) falls within the range of 50 to 300, and the peak intensity of the orientation layer is greater than I (002) / I (110) Falls in the range of 10 to 200.
[0178] Table 3
[0179]
[0180] As shown in Table 3, Examples 1 to 3 in which the surface layer is an oriented layer and the active material layer includes three or more layers exhibit excellent high-rate charge and discharge characteristics. However, Comparative Example 1 having two layers regardless of including an oriented layer and Comparative Example 2 in which an oriented portion and a non-oriented portion are formed in one layer rather than separate layers exhibit deteriorated high-rate charge and discharge cycle life characteristics.
[0181] *BET Reviews
[0182] The lithium secondary battery cells according to Examples 1 to 3 and Comparative Examples 1 and 2 were charged and discharged at 0.1C and fully discharged to 3V, and then disassembled to obtain the negative electrode. The negative electrodes were used to obtain respective samples of 5 cm × 5 cm in size, which were cut into 0.5 cm × 0.5 cm in size and placed in a BET sample holder, and then their BET was measured by nitrogen adsorption method, and the results are shown in Table 4.
[0183] Table 4
[0184] <![CDATA[BET(m 2 / g)]]> Example 1 0.71 Example 2 0.72 Example 3 0.69 Comparative Example 1 0.75 Comparative Example 2 0.73
[0185] *Cycle life characteristics evaluation
[0186] The full batteries of Examples 1 to 3 and Comparative Examples 1 and 2 were charged at constant current / constant voltage at 1.0C, 4.4V, and 0.1C cutoff, paused for 5 minutes, and discharged at constant current at 1.0C and 3.0V cutoff and paused for 5 minutes as one cycle, and the cycle was repeated 300 times. The capacity retention rate depending on the charge and discharge cycle was evaluated by calculating the discharge capacity ratio of each cycle relative to the discharge capacity of the first cycle.
[0187] The results are shown in Table 5.
[0188] Table 5
[0189] Cycle characteristics (%) Example 1 80 Example 2 79.5 Example 3 78.9 Comparative Example 1 70.5 Comparative Example 2 62.1
[0190] As shown in Table 5, the batteries including a negative electrode in which the active material layer includes three or more layers and the surface layer is an oriented layer according to Examples 1 to 3 exhibit excellent cycle life characteristics compared to a battery having two active material layers (Comparative Example 1) or a battery having one layer in which an oriented portion and a non-oriented portion are formed (Comparative Example 2).
[0191] While the present disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: current collector; as well as a negative electrode active material layer, formed on the current collector and comprising a carbon-based negative electrode active material, wherein the negative electrode active material layer has a multilayer structure of three or more layers, At least one layer of the negative electrode active material layer is an oriented layer having a DD value of 19 or more defined by Equation 1: [Equation 1] DD=(I a / I 总 )×100 In equation 1, DD represents the divergence, I a is the sum of the peak intensities at 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2° measured by XRD using CuKα radiation, and I 总 It is the sum of peak intensities at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° measured by XRD using CuKα rays.
2. The negative electrode for a lithium secondary battery according to claim 1, wherein: The negative electrode active material layer has a multilayer structure of three to five layers.
3. The negative electrode for a lithium secondary battery according to claim 1, wherein: The negative active material layer having the multilayer structure of three or more layers includes an inner layer in contact with the current collector, a surface layer, and at least one intermediate layer between the inner layer and the surface layer, and the surface layer is the alignment layer having the DD value of 19 or more.
4. The negative electrode for a lithium secondary battery according to claim 1, wherein: The alignment layer has a DD value of 19 to 60.
5. The negative electrode for a lithium secondary battery according to claim 1, wherein: At least one layer is a non-oriented layer having the DD value less than 19.
6. The negative electrode for a lithium secondary battery according to claim 1, wherein: The peak intensity is the peak integrated area value.
7. The negative electrode for a lithium secondary battery according to claim 1, wherein: The peak intensity ratio of the negative electrode at the (002) plane to the (110) plane measured by XRD using CuKα radiation is I (002) / I (110) It is between 50 and 300.
8. The negative electrode for a lithium secondary battery according to claim 1, wherein: The peak intensity ratio I of the orientation layer at the (002) plane relative to the (110) plane measured by XRD using CuKα radiation is (002) / I (110) It is 10 to 200.
9. The negative electrode for a lithium secondary battery according to claim 1, wherein: The peak intensity ratio I of the non-oriented layer at the (002) plane relative to the (110) plane measured by XRD using CuKα rays is (002) / I (110) It is between 200 and 500.
10. The negative electrode for a lithium secondary battery according to claim 1, wherein: The negative electrode active material layer has a total thickness of 100 μm to 1000 μm.
11. The negative electrode for a lithium secondary battery according to claim 1, wherein: The carbon-based negative electrode active material is artificial graphite or a mixture of artificial graphite and natural graphite.
12. The negative electrode for a lithium secondary battery according to claim 1, wherein: The negative electrode active material layer further includes Si-based negative electrode active material, Sn-based negative electrode active material, lithium vanadium oxide or a combination thereof.
13. A lithium secondary battery, comprising: The negative electrode according to any one of claims 1 to 12; positive electrode; as well as Electrolytes.
14. The lithium secondary battery according to claim 13, wherein: The lithium secondary battery is a high-power battery.
